Job Performance among Nursing Staff at Tishreen University Hospital (Journal of Hama University, 2022)
Job performance is the common denominator of all efforts made by management and individuals and the end product of the outcome of their activities within the framework of the organization, as it constitutes par excellence its most important objectives, and the efficiency of performance in any organization or sector depends on the level of performance and practices of its human resources.The research aimed to identify the level of job performance among nursing staff and its relationship with some demographic variables at Tishreen University Hospital in Lattakia city.A descriptive analytic study was performed using random sample included (300) nurses from nursing staff in Tishreen University Hospital, the researcher adopted the tool of research. The tool included two main parts; Includes demographic data, and job performance scale.The results showed a high level of job performance, statistical relationship between job performance and age& marital status.Working to maintain the current level of performance by giving the employees a moral motive, enhancing their confidence, enhancing the initiative spirit among the employees, and prompting them to think of solutions to the problems they face and discuss them at the collective level, with the aim of developing performance.